Innovation in Mathematics Learning Through E-Learning Ethnomathematics: Creative Thinking Skills and Learning Outcomes - Rosidin, Rosidin; Firdaus, Rangga; Anantanukulwong, Roseleena; Kinda, Johanis (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study aims to develop ethnomathematics-based e-learning with a touch of Lampung cultural design and analyze its influence on students’ creative thinking skills and learning outcomes in a number of materials. E-learning based on ethnomathematics was developed using the Branch development model with stages of development, implementation, and evaluation. The research sample consisted of 80 students selected through purposive sampling techniques. The data collection instrument was an essay test to measure students’ creative thinking skills and learning outcomes. The data were analyzed using an independent sample t-test statistical test with the help of SPSS 25 software. The results of the analysis showed that the t-value for creative thinking skills (14.426) and learning outcomes (13.921) were higher than the t table (1.990) at a significance level of 0.05. This indicates a significant difference between the experimental and control groups. The average increase in creative thinking skills reached 67.5%, while student learning outcomes increased by 65.0%. This e-learning enhances the originality and elaboration aspects of creative thinking and provides a learning experience that enriches mathematical knowledge through the Lampung cultural context. E-learning based on ethnomathematics with Lampung design offers innovation in digital learning that is not only adaptive to the needs of the 21st century but also supports the preservation of local culture in the educational process. This study recommends ethnomathematics-based e-learning as an alternative learning medium that effectively improves creative thinking skills and student learning outcomes while introducing Lampung culture more broadly in an academic context